2017
DOI: 10.1177/1708538117724933
|View full text |Cite
|
Sign up to set email alerts
|

A clinical review of early outcomes from contemporary flow modulation versus open, fenestrated and branch technologies in the management of thoracoabdominal aortic aneurysm

Abstract: Traditional therapeutic options for complex thoracoabdominal aneurysm include open repair, hybrid repair or endovascular repair (involving fenestrated or branched endografts). The Streamliner Multilayer Flow Modulator has been available for treatment of thoracoabdominal aneurysms since 2010. Its design permits blood flow to perfuse through the mesh in a modus that preserves collateral branch patency, while modulating turbulent to laminar flow within the device. The flow then stagnates over time within the surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Modified approaches have been described that eliminate the need for open repair whereby the ascending aorta is replaced first with a trifurcated side-branch for debranching of the arch in a sequential manner to a level that is accessible for clamping; however, no studies have yet shown the benefit of such an approach. Although it does add to the cardiopulmonary bypass time and blood loss, 4,5 the addition of a hemiarch has been shown not to increase the risk of the procedure. However, this noninferiority is lost when the proximal arch is disease free, with exception of an underlying aortopathy in which the normal-sized arch will predictively enlarge or dissect at a later time; in this setting, a hemiarch is justified.…”
Section: Aneurysmsmentioning
confidence: 99%
“…Modified approaches have been described that eliminate the need for open repair whereby the ascending aorta is replaced first with a trifurcated side-branch for debranching of the arch in a sequential manner to a level that is accessible for clamping; however, no studies have yet shown the benefit of such an approach. Although it does add to the cardiopulmonary bypass time and blood loss, 4,5 the addition of a hemiarch has been shown not to increase the risk of the procedure. However, this noninferiority is lost when the proximal arch is disease free, with exception of an underlying aortopathy in which the normal-sized arch will predictively enlarge or dissect at a later time; in this setting, a hemiarch is justified.…”
Section: Aneurysmsmentioning
confidence: 99%
“…Concerning the application of MFM in aortic Z2 lesions, some clinicians have made bold attempts and achieved good short-term results. This technology not only seals the aortic intima groove with a traditional endograft, but also guides the blood ow into the branches, without blocking the main branches of the supraarch artery [41]. In this study, compared with the stent-free model, it is considered that the MFM has little effect on the blood ow of the subclavian artery branch.…”
Section: Discussionmentioning
confidence: 99%
“…A case report was published that described the emergency use of MFM for the treatment of aortic dissection, outside the indications for use [ 15 ]. The most extensive experience with the MFM technique was reported by Sultan et al [ 12 , 16 , 17 ]. Several published papers describe findings from in-vitro [ 16 ], animal [ 17 ], and early clinical studies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most extensive experience with the MFM technique was reported by Sultan et al [ 12 , 16 , 17 ]. Several published papers describe findings from in-vitro [ 16 ], animal [ 17 ], and early clinical studies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%